2020
DOI: 10.3389/fcell.2020.00838
|View full text |Cite
|
Sign up to set email alerts
|

Propofol Exposure Disturbs the Differentiation of Rodent Neural Stem Cells via an miR-124-3p/Sp1/Cdkn1b Axis

Abstract: Accumulating studies have indicated that propofol may lead to neurotoxicity and its effect on neural stem cells (NSCs) may play pivotal role in propofol-related neurotoxicity. Previously, we found that propofol could promote NSCs proliferation and could regulate several microRNA expressions. However, the underlying mechanism between microRNAs and NSCs development after propofol exposure is still unclear. Our data first observed that rat primary neural stem cells exposed to propofol exhibited a cell cycle arres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…For example, in in vivo and in vitro models, Pearn et al found that propofol induced neurotoxicity by the loss of RhoA-dependent dendritic spines and impaired retrograde axonal transport of BDNF [ 19 ]. An in vivo study by Cao et al demonstrated that propofol changes the differentiation of neural stem cells (NSCs) through the miR-124/SP1/CDKN1B axis, resulting in neuronal damage [ 20 ]. Consistent with the above findings, we found that propofol was cytotoxic and caused apoptosis in HT22 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in in vivo and in vitro models, Pearn et al found that propofol induced neurotoxicity by the loss of RhoA-dependent dendritic spines and impaired retrograde axonal transport of BDNF [ 19 ]. An in vivo study by Cao et al demonstrated that propofol changes the differentiation of neural stem cells (NSCs) through the miR-124/SP1/CDKN1B axis, resulting in neuronal damage [ 20 ]. Consistent with the above findings, we found that propofol was cytotoxic and caused apoptosis in HT22 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Our study consisted of a cell line culture, which may have prevented us from investigating the actual effects of propofol on neurons. Second, we used cell death as the final endpoint; however, propofol may adversely affect surviving neurons that in turn affect cell function, such as disrupt the differentiation of NSCs [ 20 ] and impair hippocampal synaptic plasticity [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…132 In terms of cell cycle and differentiation, a study demonstrated that propofol exposure induces a cell cycle arrest status and an inclination to differentiate into GFAPpositive or S100β-positive cells by inhibiting miR-124-3p/Sp1/ cdkn1b axis. 133 GFAP is a symbol of stemness or astrocyte, and S100β is a marker of folliculo-stellate cells. Specificity protein 1 (SP1) is a transcription factor involved in regulating the cell cycle, 134 which can control the transcription of cyclindependent kinases inhibitors (CDKIs).…”
Section: Impairment In the Motormentioning
confidence: 99%
“…In terms of cell cycle and differentiation, a study demonstrated that propofol exposure induces a cell cycle arrest status and an inclination to differentiate into GFAP-positive or S100β-positive cells by inhibiting miR-124-3p/Sp1/cdkn1b axis . GFAP is a symbol of stemness or astrocyte, and S100β is a marker of folliculo-stellate cells.…”
Section: Mechanisms Of Propofol-induced Developmental Neurotoxicitymentioning
confidence: 99%
“…Two miRNA clusters (Gabbr1 and Cacna1b and Gabbr2), which exhibited differential expression upon exposure, may simultaneously regulate multiple genes in a coordinated manner during NSC development 47 . Inhibition of NSCs' neurogenesis is associated with the miR‐141‐3p/IGF2BP2 axis, 48 while perturbation of differentiation is related to the miR‐124‐3p/Sp1/cdkn1b axis 18 . However, the mechanism of propofol's action on miRNA and its target genes remains to be elucidated, especially on neurons 42 .…”
Section: Effects Of Anesthetic Drugs On Nscs and Their Mechanismsmentioning
confidence: 99%